Numerical Investigation of Liquid Carryover in T-Junction with Different Diameter Ratios - Pao, W. (Institute of Physics Publishing, 2018)
In offshore Malaysia, T-junction is installed at the production header as a compact separator to tap produced gas from reservoir as fuel gas for power generation. However, excessive liquid carryover in T-junction presents a serious operational issue because it trips the whole production platform. The primary objective of present study is to numerically investigate the liquid carryover due to formation of slug, subsequently its liquid carryover at different diameter ratio. The analyses were carried out on a model with 0.0254 m (1 inch) diameter horizontal main arm and a vertically upward side arm using Volume of Fluid Method. Three different sides to main arm diameter ratio of 1.0, 0.5 and 0.3 were investigated with different gas and liquid superficial velocities. The results showed that, while the general trend is true that smaller diameter ratio T-junction has lesser liquid take off capacity, it has a very high frequency of low liquid carryover threshold. In other words, under slug flow, smaller diameter ratio T-junction is constantly transporting liquid even though at a lesser volume in comparison to regular T-junction. Â© Published under licence by IOP Publishing Ltd.